Adapting Experiential Learning in Times of Uncertainty: Challenges, Strategies, and Recommendations Moving Forward - O'Connor, Eileen; Marcogliese, Emily; Anis, Hanan; Faye, Gaëlle; Flynn, Alison; Hayman, Ellis; Stambouli, Jamel (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
Experiential learning offers students the opportunity to gain practical experience with a community or industry partner in their field of study. During the Covid-19 pandemic, many workplaces transitioned from in-person to at-home work environments, and those that did not, often reduced or removed access for non-essential personnel. In this report from the field, multiple viewpoints are shared that emerged from an interdisciplinary panel on experiential learning in the June 2022 Spotlight Series hosted by Teaching and Learning Support Services at the University of Ottawa. These voices “from the field” shed light on the impact of uncertain times on experiential learning and, collectively, focus on identifying challenges, implementing strategies and good practices, and sharing recommendations moving forward.